Diagnostic characteristics of supplemental laboratory criteria for incomplete Kawasaki disease in children with complete Kawasaki disease - Hyun Ok Jun; Jeong Jin Yu; So Yeon Kang; Chang Deok Seo; Jae Suk Baek; Young-Hwue Kim; Jae-Kon Ko (Korean Pediatric Society, 2015)
PurposeIn 2004, the American Heart Association (AHA) had published an algorithm for the diagnosis of incomplete Kawasaki disease (KD). The aim of the present study was to investigate characteristics of supplemental laboratory criteria in this algorithm.MethodsWe retrospectively examined the medical records of 355 patients with KD who were treated with intravenous immunoglobulin (IVIG) during the acute phase of the disease. Laboratory data were obtained before the initial IVIG administration and up to 10 days after fever onset. In 106 patients, laboratory testing was performed more than twice.ResultsThe AHA supplemental laboratory criteria were fulfilled in 90 patients (25.4%), and the frequency of laboratory examination (odds ratio [OR], 1.981; 95% confidence interval [CI], 1.391-2.821; P<0.001) was a significant predictor of it. The fulfillment of AHA supplemental laboratory criteria was significantly associated with refractoriness to the initial IVIG administration (OR, 2.388; 95% CI, 1.182-4.826; P=0.013) and dilatation of coronary arteries (OR, 2.776; 95% CI, 1.519-5.074; P=0.001).ConclusionRepeated laboratory testing increased the rate of fulfillment of the AHA supplemental laboratory criteria in children with KD.